PENERAPAN PIJAT BAYI TERHADAP PENINGKATAN KUALITAS TIDUR BAYI DI PRAKTIK MANDIRI BIDAN EKA SRIWAHYUNI MEDAN - Sriwahyuni, Eka (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Baby massage is a gentle stroking or massaging therapy for babies, this is stimulation through tactile stimulation, gentle massage approaching soft and gentle massage on the surface of the baby's skin gently, on the tissues and organs of the body. According to data from the 2012 World Health Organization, it is stated that 33% of babies experience sleep problems (WHO, 2012). The aim of carrying out community service in the form of a baby massage application is to improve the quality of sleep for babies at Midwife Eka Sriwahyuni's Independent Practice. The method used is to apply direct massage to babies who experience sleep quality problems, which is known from the results of interviews with their mothers. From the results of applying baby massage, it was found that the majority of babies experienced an increase in sleep quality by 70% and only 11% less. The conclusion of this activity is that community service activities in the form of baby massage carried out at the Independent Midwife Practice Eka Sriwahyuni ​​Medan, can be used as a solution to improve the quality of baby sleep which will have a positive effect on the growth and development of other babies